Universal access at crossroads: A political economy of the digital migration policies in South Africa - Nkuna, Jabulani (My University, 2014)
The objective of this study was to investigate how economic and political power relations between organisations involved in the digital migration influence the control of the policy process. Therefore, the research investigated whether the policies of digital migration are driven by profit motives or the need to accelerate universal access for television. The research applied the theoretical approach of critical political economy of the media, the Marxist ideology, global governance theories, and policy network theories in order to generate critical and analytical judgement for the research problem. In terms of methodology, the study applied qualitative research methodology by using a combination of document analysis and participant observation. In order to understand the political and economic context of digital migration policies, an analysis of documents such as policies, policy submissions; parliamentary briefings and press reports was conducted. The researcher also conducted participant observation in various seminars and public hearings. The findings reveals that digital migration in South Africa was pushed by international forces which seek to benefit in terms of trading digital content and electronic equipment. It is not surprising that digital migration policy making in South African context is dominated by economic players with profit motives. Broadcasters, manufacturers and other actors who have a significant interest on digital migration are influencing policies which will benefit them financially thus ignoring universal access goals. The relationship between government and other stakeholders is a stable one as powerful economic players maintain a close relationship in order to influence policies. It appears that it will be very difficult for government to attain universal access of television while powerful economic players have major say whenever new policies are made.